2018
DOI: 10.1002/adsc.201800161
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Cobalt‐Catalyzed C−H Bond Functionalizations by Ball Milling

Abstract: Ball milling techniques have been applied in the development of a mechanosynthesis of [Cp*Co(CO)I2], which proved highly efficient as catalyst in mechanochemical C−H bond amidations of indoles in a mixer ball mill. A wide range of amidated products is obtained in excellent yields. Compared to the solution‐based methods, the procedure opens a more feasible and environmentally‐friendly access to both the cobalt(III) catalyst and 2‐amidated indoles.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 71 publications
0
36
0
1
Order By: Relevance
“…Hence, the best milling additive for a reaction would strongly depend on the desired transformation itself, and the selection of the milling‐aid should come after a careful screening. Finally, if column chromatography becomes inevitable to isolate the product, sometimes a final short milling of the reaction mixture with additives such as silica gel or alumina (if compatible) can enable an easy recovery of the reaction mixture impregnated in the stationary phase [112] . This simple step can directly cut down solvent waste and it would directly reduce energy consumption (e. g., by avoiding solvent evaporation), a topic that lies at the heart of the discussion presented in GC 6.…”
Section: Mechanochemistry and The Twelve Principles Of Green Chemistrymentioning
confidence: 99%
“…Hence, the best milling additive for a reaction would strongly depend on the desired transformation itself, and the selection of the milling‐aid should come after a careful screening. Finally, if column chromatography becomes inevitable to isolate the product, sometimes a final short milling of the reaction mixture with additives such as silica gel or alumina (if compatible) can enable an easy recovery of the reaction mixture impregnated in the stationary phase [112] . This simple step can directly cut down solvent waste and it would directly reduce energy consumption (e. g., by avoiding solvent evaporation), a topic that lies at the heart of the discussion presented in GC 6.…”
Section: Mechanochemistry and The Twelve Principles Of Green Chemistrymentioning
confidence: 99%
“…The first of these studies towards the catalytic mechanochemical C−H bond functionalizations was reported in 2015 by Bolm and co‐workers, who used a rhodium(III) complex to catalyze an oxidative Heck‐type reaction in a ball mill . More recently, mechanochemistry has also been applied to the transition‐metal‐catalyzed halogenation, amination,,, olefination, arylation, allylation, alkynylation, and oxidative cyclization of C−H bonds. However, to the best of our knowledge, a mechanochemical C−H borylation reaction has not been reported to date, even if the development of such a catalytic C−H borylation would be particularly attractive from an industrial perspective.…”
Section: Methodsmentioning
confidence: 99%
“…[86] 和吴勇课题 组 [87] 分别独立的报道了三氮唑导向的芳基碳氢键酰胺 化反应(Scheme 35, c). 值得一提的是, Bolm 课题组 [88] 在 2018 年通过球磨机械化学在嘧啶导向下实现了吲哚 2 位碳氢键的酰胺化反应. 2018 年游书力课题组 [89] [91] 也通过亚胺导向实现碳氢键胺化反应构建 喹唑啉类化合物(Scheme 36, b).…”
Section: 以羟胺及其衍生物为胺化试剂unclassified